2022
DOI: 10.1111/faf.12674
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better use of fisheries data in spatial planning

Abstract: In the search for protecting biodiversity, enhancing sustainable resource use, and minimizing conflict among users, spatial planning is now ubiquitous around the globe.Acquiring maps of fishing activity is critical to account for the interests of fishers, but fisheries are generally underrepresented in spatial plans. We conducted a quantitative systematic literature review on how fisheries data have been included in spatial planning. 145 research articles were reviewed. Most studies (99%) assessed marine ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…The analysis presented here, however, incorporates only 1 year of data and represents only a snapshot. Long-term patterns of fishing activity should be assessed for using this information in drafting robust spatial plans and management decisions (Chollett et al in 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis presented here, however, incorporates only 1 year of data and represents only a snapshot. Long-term patterns of fishing activity should be assessed for using this information in drafting robust spatial plans and management decisions (Chollett et al in 2022).…”
Section: Discussionmentioning
confidence: 99%
“…When revenue, effort, and catch information are all available, revenue measures are generally preferred as a metric for depicting the relative importance of an area for fishing, because effort measures cannot gauge how effective vessels and gears are at capturing fish, and catch measures fail to capture the difference in value across species (Jin et al 2013). In any case, the variable used should match closely the management objectives to ensure the ecological and/or social sustainability of the resulting plan (Chollett et al 2022). For example, when planning for offshore wind areas, Bastardie et al (2015) found fishing effort to be the most relevant variable to use to ensure social sustainability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies concerning spatial distribution relationships, a critical aspect that needs to be addressed is the rational planning of spatiotemporal scales [22]. In different application scenarios, the optimal spatiotemporal scales for different model outcomes may vary [23].…”
Section: Introductionmentioning
confidence: 99%